GC-MS Analysis: In Vivo Hepatoprotective and Antioxidant Activities of the Essential Oil of Achillea biebersteinii Afan. Growing in Saudi Arabia. (12th May 2016) - Al-Said, Mansour S.; Mothana, Ramzi A.; Al-Yahya, Mohammed M.; Rafatullah, Syed; Al-Sohaibani, Mohammed O.; Khaled, Jamal M.; Alatar, Abdulrahman; Alharbi, Naiyf S.; Kurkcuoglu, Mine; Baser, Husnu C.
Abstract : Liver disease is a worldwide problem. It represents one of the main causes of morbidity and mortality in humans. Achillea biebersteinii is used as herbal remedy for various ailments including liver diseases. But the scientific basis for its medicinal use remains unknown. Thus, this research was undertaken to evaluate the efficiency of A. biebersteinii essential oil (ABEO) (0.2 mL/kg) in the amelioration of CCl4 -induced hepatotoxicity in rodent model. Moreover, the chemical content of the oil was investigated using GC and GC-MS. The following biochemical parameters were evaluated: serum glutamic oxaloacetic transaminase (GOT), glutamic-pyruvic transaminase (GPT), gamma-glutamyl-transpeptidase ( γ -GGT), alkaline phosphatase (ALP), and total bilirubin. Furthermore, lipid profile, malondialdehyde (MDA), nonprotein sulfhydryl (NP-SH), and total protein (TP) contents in liver tissue were estimated. 44 components (92.0%) of the total oil have been identified by GC-MS analysis where α -terpinene andp -cymene were the most abundant. The high serum enzymatic (GOT, GPT, GGT, and ALP) and bilirubin concentrations as well as the level of MDA, NP-SH, and TP contents in liver tissues were significantly reinstated towards normalization by the ABEO. Histopathological study further confirmed these findings. In addition, ABEO showed mild antioxidant activity in 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging and β -carotene-linoleic acid assays.